2016
DOI: 10.1175/jamc-d-15-0227.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Variation in Surface Solar Irradiance and Clustering of Observation Stations in Japan

Abstract: Variation in surface solar irradiance is investigated using ground-based observation data. The solar irradiance analyzed in this paper is scaled by the solar irradiance at the top of the atmosphere and is thus dimensionless. Three metrics are used to evaluate the variation in solar irradiance: the mean, standard deviation, and sample entropy. Sample entropy is a value representing the complexity of time series data, but it is not often used for investigation of solar irradiance. In analyses of solar irradiance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…As usual, complexity in a solar irradiation time series stands for randomness or disorder. In order to identify the underlying behaviour of these two concepts, there are various methods to study the behaviour of solar irradiation time series [ 16 , 23 , 26 ]. In the framework of Kolmogorov complexity, we have focused on the need to delineate the predictability of solar irradiation.…”
Section: Study Locations and Pyranometer Measurementsmentioning
confidence: 99%
“…As usual, complexity in a solar irradiation time series stands for randomness or disorder. In order to identify the underlying behaviour of these two concepts, there are various methods to study the behaviour of solar irradiation time series [ 16 , 23 , 26 ]. In the framework of Kolmogorov complexity, we have focused on the need to delineate the predictability of solar irradiation.…”
Section: Study Locations and Pyranometer Measurementsmentioning
confidence: 99%
“…The prior probability distributions employed within the MC method inherently link light absorption measurements and computed mass column density and emissions using sky-LOSA; as such, in keeping with Andreae and Gelencsér (2006) and Petzold et al (2013), sky-LOSA-inferred soot-BC mass might therefore be called "equivalent BC" as is recommended for all light-absorption-based diagnostics, especially where absorption-enhancing non-BC material may be present. For the case of flare-generated soot-BC however, studies in the field (Schwarz et al, 2015;Weyant et al, 2016) have identified that the presence of non-BC aerosols in flare plumes is "not statistically different from zero" (Weyant et al, 2016), which is supported by laboratory observations (e.g., Kazemimanesh et al, 2019). This justifies use of soot property probability distributions derived from literature data of freshly emitted soot particulate by Johnson et al (2013).…”
Section: Introductionmentioning
confidence: 58%
“…For CIE sky models with an unobstructed sun (types 7-15), ξ ED (a) ∼ U (0.75, 1.25), and for models with an obstructed sun (types 1-6), ξ ED (a) ∼ U (0, 1.25). These prior distributions of ξ ED (a) were based on observations by Watanabe et al (2016), who studied the "clearness index" (ground-level horizontal normalized by extraterrestrial horizontal irradiance) over 5 years at 47 observation stations across Japan. They found that the relative variation in the clearness index was approximately 4.3 % for skies with unobscured suns and 35 % for skies with obscured suns; corresponding variance-equivalent uniform distributions would have a range of 15 % and 121 %, respectively.…”
Section: (A4)mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the geographical locations, the next best approach to generate characteristics is using statistics. Watanabe et al (2016) used sample mean, variance and entropy to evaluate the variation in solar irradiance. Woyte et al (2007) used a wavelet-based localized spectral analysis to identify and classify the fluctuations in time series of the instantaneous clearness index.…”
Section: Choice Of Featuresmentioning
confidence: 99%